PERAN SBSN DALAM KEBIJAKAN MONETER SYARIAH: STUDI ATAS OPERASI PASAR TERBUKA OLEH BANK INDONESIA - Laili, Sasmita Nurvinda (LPPM STAI Muhammadiyah Probolinggo, 2025)
The existence of State Sharia Securities (SBSN) as a sharia financial instrument shows great potential not only in financing development, but also in implementing sharia-compliant monetary policies. Through Sharia Open Market Operations (S-OMO), Bank Indonesia can manage liquidity conditions in the sharia money market flexibly and effectively. SBSN purchase or sale transactions in the secondary market allow Bank Indonesia (BI) to inject or absorb liquidity in accordance with economic dynamics, while maintaining macroeconomic stability. However, there are obstacles such as limited SBSN liquidity in the secondary market and suboptimal policy coordination between fiscal and monetary authorities. For this reason, stronger policy synergy is needed, increasing the number and types of liquid SBSN, and educating market players so that the use of SBSN in monetary policy can be maximized and have a broad impact on national economic stability.